Rehabilitation Efficacy of Gait Induced Functional Electrical Stimulation Combined with Body-Weight Supported Treadmill Training on Children with Spastic Cerebral Palsy - SONG Wei; ZHONG Yue; KE Xiaohua; HUANG Dunbing; ZHANG Anren; DONG Xiaoli (康复学报)
ObjectiveTo observe the effect of gait induced functional electrical stimulation (FES) combined with body-weight supported treadmill training (BWSTT) on gross motor function and walking function of children with spastic cerebral palsy (SCP).MethodsA total of 60 children with spastic cerebral palsy in the Shanghai Fourth People's Hospital Affiliated to Tongji University from March 2022 to March 2023 were randomly divided into control group, BWSTT group and combined intervention group according to a randomized sequence by SAS software, with 20 cases in each group. The control group received conventional rehabilitation therapy, once a day, 40 minutes a time, five days a week, lasting for eight weeks. The BWSTT group received body-weight supported treadmill training in addition to the training of the control group. The slope of the plate was 0°, the initial speed was 0.09 m/s, and the increment of 0.03 m/s was gradually adjusted to the appropriate speed that the child could walk with. The initial weight support was 30% of the child's body mass, and it was gradually adjusted to fully support the child's own body mass. The combined intervention group received gait induced FES in addition to the training of the BWSTT group. A low-frequency electronic pulse stimulator was used to stimulate the common peroneal nerve and anterior tibialis muscle of the children, and the stimulation intensity was set at the desirable movements of ankle dorsiflexion and valgus, and could be tolerated by the children, once a day, 20 minutes a time, five days a week, lasting for eight weeks. Before and after treatment, D (standing) and E (walking, running and jumping) zones of the 88-item gross motor function measurement 88 (GMFM-88) was used to assess the children's gross motor function; six-minute walking test (6MWT) was used to assess walking function; physiological expenditure index (PCI) was used to evaluate walking efficiency; and gait parameters of the children (such as stride length, stride width and stride speed) were analyzed.ResultsCompared with that before treatment, GMFM-D and GMFM-E scores, 6MWT, stride length and stride speed were significantly higher and PCI and stride width were significantly lower in the three groups after treatment, and the differences were statistically significant (P<0.05). Compared with the control group, GMFM-D and GMFM-E scores, 6MWT, stride length and stride speed were significantly higher, and PCI and stride width were significantly lower in the BWSTT group and the combined intervention group after treatment, and the differences were statistically significant (P<0.05). Compared with the BWSTT group, the GMFM-D, GMFM-E scores, 6MWT, stride length and stride speed were significantly higher, and PCI and stride width were significantly lower in the combined intervention group after treatment, and the differences were statistically significant (P<0.05).ConclusionGait-induced FES combined with BWSTT can improve motor function, correct abnormal gait, and improve walking efficiency in children with SCP, which is recommended for clinical application.